Diet/lifestyle and risk of diabetes and glycemic traits: a Mendelian randomization study - Ding, R.; Huang, T.; Han, J. (Lipids Health DisLipids Health DisLipids Health Dis, 2018)
BACKGROUND: Observational studies have demonstrated diet/lifestyle play roles in development of type 2 diabetes (T2DM); however, it remains unclear whether these relationships are causal. METHODS: A two-sample MR approach was used to examine the causal effect of diet/lifestyle upon risk of T2DM and glycemic traits. RESULTS: The protein intake-increasing allele C of FTO was significant associated with higher risk of T2DM (Beta +/- SE = 0.104 +/- 0.014, P = 4.40 x 10(- 11)), higher level of HOMA-IR (Beta +/- SE = 0.016 +/- 0.004, P = 9.55 x 10(- 5)), HOMA-B (Beta +/- SE = 0.008 +/- 0.003, P = 0.020). Using MR analyses, increased protein intake was causally associated with an increased risk of T2DM (Beta +/- SE = 0.806 +/- 0.260, P = 0.002). In addition, smoking cessation was causally associated with increased levels of glycemic traits such as HOMA-IR (Beta +/- SE = 0.165 +/- 0.072, P = 0.021), fasting insulin (Beta +/- SE = 0.132 +/- 0.066, P = 0.047) and fasting glucose (Beta +/- SE = 0.132 +/- 0.064, P = 0.039). CONCLUSIONS: These results provide evidence supporting a causal role for higher protein intake and smoking cession in T2DM. Our study provides further rationale for individuals at risk for diabetes to keep healthy lifestyle.
Keywords: *Smoking Cessation; Alpha-Ketoglutarate-Dependent Dioxygenase FTO/*genetics; Diabetes Mellitus, Type 2/etiology/*genetics/metabolism; Diet, High-Protein/*adverse effects; Humans; Life Style; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide